Authority Control of Names in Local Digitization Projects and the Eastern North Carolina Postcard Collection - Dragon, Patricia M. (East Carolina University, 2009)
Authority control is a vitally important but frequently overlooked aspect of metadata creation for local digitization projects. The addition of digital projects metadata to the traditional cataloging environment creates a number of challenges for authority control, challenges arising in turn from the nature of the materials being digitized, from choices made during the project, and from the tools used for the project. By examining the authority control applied to named entities in the Eastern North Carolina Postcard Collection at East Carolina University, this paper describes these challenges in some detail, and also describes attempts to overcome them.
Keywords: Metadata; Cultural heritage; Images; Subject analysis; Cataloging